An Additive Manufacturing Spare Parts Inventory Model for an Aviation Use Case. Issue 1 (2nd January 2019) - Togwe, Thembani; Eveleigh, Timothy J.; Tanju, Bereket
Abstract: To maintain high service levels and mitigate long lead times, many enterprises hold large spare parts inventories. Using additive manufacturing (AM) for spare parts in aviation has been proposed previously but prior studies did not address system-specific lead time impacts. This article codifies lifecycle variables introduced by AM and presents an aviation case study. The variables highlight the value offered by AM over traditional methods. Specifically, the case study demonstrates that introducing up to 35% of AM parts to the spare parts inventory improves the system replenishment lead time by up to 33%, thus suggesting AM can be used to mitigate challenges related to spare parts management. This work also presents an approach to integrate AM into the spare parts inventory mix.